2011
DOI: 10.1590/s0102-86502011000600006
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment with pentoxifylline attenuates lung injury induced by intestinal ischemia/reperfusion in rats

Abstract: PURPOSE: To investigate the protective effect of pentoxifylline against the lung injury observed after intestinal ischemia (I) followed by a period of reperfusion (R). METHODS: Twenty-eight male Wistar rats were equally divided into 4 experimental groups and operated under ketamine-xylazine anesthesia. (1) Sham: falsely-operated animals; (2) SS+IR: intestinal ischemia was accomplished by clipping the superior mesenteric artery during 60 minutes, with an administration of a standard volume of saline solution (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 37 publications
(21 reference statements)
2
11
0
9
Order By: Relevance
“…This could be attributed to the large amount of physiological compensatory mechanisms to maintain the values of BE, BIC and pH within the normal range 23 .The lactate levels are directly and clearly related to the degree of splanchnic hypoperfusion 24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…This could be attributed to the large amount of physiological compensatory mechanisms to maintain the values of BE, BIC and pH within the normal range 23 .The lactate levels are directly and clearly related to the degree of splanchnic hypoperfusion 24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…After histological analysis according Chiu et al 20 it was demonstrated that without PTX 1,13,14,16 and PGE1 [17][18][19][20] The PGE1 [17][18][19], is known by its intense vasodilator effect, for being a substance with intense biological activity that has been used for such a longtime to treat. the chronic arterial occlusive disease, since beside to vasodilation capacity it also inhibit platelets aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…A PTX 1,13,14,16 has an antioxidant action directly inhibiting the anion superoxide that also indirectly block xanthine-oxidase enzyme activity. Therefore, it seems to decrease intensity of inflammatory response reducing neutrophils migration to the local area, decreasing liberation of cytokines, of tumoral necrosis factor, platelet activator factor and endothelin among other factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations